The Judiciary in discourse. Controversies in the presentation of the Project for the Democratization of Justice in Argentina - Gindin, Irene Lis (2022)
Faced with the advanced of the judicialization of politics - and the politicization of justice - this article set out to recreate a controversial scene. Controversy, debate, litigation, polemic, were categories used in this text to characterize the exchange –both political and journalistic– around the "Project for the Democratization of Justice" presented by the former president of the Argentine Nation, Cristina Fernández de Kirchner, in 2013. To do this, we have analyzed the news related to the project of three national newspapers (Clarín, La Nación and Página / 12) and put them in tension with the properly political discourse. What is important at this point does not consist of verifying whether the study actually corresponds to a Lawfare process or, conversely, to an attempt by a certain government to intercede –for political party purposes– in the correct functioning of justice. Rather, how those political-judicial processes that we study appear thus thematized in the Argentine public scene. The materials were analysed considering, as a hypothesis, that the discussion is structured around three axes: a) The moment in which the reform is proposed; b) The discussion on its constitutionality; c) The debate on the division of powers.